Pengaruh Website Design, Customer Service, Security Privacy terhadap Overall e-Service Quality: (Studi Kasus pada Pengguna Shopee Yogyakarta) - Sopran, Cepi; Lukitaningsih, Ambar; Ningrum, Nonik Kusuma (Jurnal Bingkai Ekonomi (JBE), 2022)
This study aims to explain the effect of Web Design, Customer Service and Security Privacy on Overall e-Service Quality. This study uses four variables, namely Web Design, Customer Service and Security Privacy as independent variables, and Overall e-Service Quality as dependent variables. The population in this study is Consumers who buy at Shopee at least (one) time. Sampling method using purposive sampling by collecting data using questionnaires. The results show that partially Web Design has a positif significant effect on Overall e-Service Quality, Customer Service has no significant effect on Overall e-Service Quality, and Privacy Security has a positif significant effect on Overall e-Service Quality, Web Design, Customer Service, Privacy Security significant effect on Overall e-Service Quality.